The The Fraud Pentagon Analysis In Financial Companies On The Indonesia Stock Exchange - Yosef, Maria Christa; Sumarna, Alfonsa Dian (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This research was conducted to examine the effect of the fraud pentagon theory developed by Crowe Horwath on the possibility of fraud in financial statements. The sample used in this study came from 105 financial companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. Sampling was carried out using the purposive sampling method. The data analysis method is logistic regression test analysis, processed using the Eviews application. The Pentagon theory posits five key factors: pressure, opportunity, competence, arrogance, and rationalisation. Our analysis revealed that while pressure and opportunity, as proxied by financial targets, stability, external pressure, and ineffective supervision, did not significantly influence fraud risk, the quality of the external auditor emerged as a significant determinant. Conversely, changes in auditors (rationalisation), directors (competence), and the frequency of CEO pictures (arrogance) did not appear to be significant predictors of fraud. This study suggests that external audit quality is more significant in preventing financial statement fraud than the traditional fraud triangle (pressure, opportunity, rationalisation) or other factors like competence and arrogance.